Manajemen Kegiatan Ekstrakurikuler dalam Pencapaian Prestasi Siswa (Studi Kasus di SMA Muhammadiyah 2 Al-Mujahidin Balikpapan) - Agus Mujahidin; Fitri Nur Mahmudah; Solihin (Syntax Corporation Indonesia, 2023)
The main objective of this study is to explain how to manage an extracurricular team to achieve skilled worker status at SMA Muhammadiyah 2 Al-Mujahidin Balikpapan. But the specific aims of this study are to: 1) explain how extracurricular teams are planned and run; 2) describes how the team is monitored and assessed; and 3) explain things that support and hinder extracurricular activities. The descriptive qualitative research method was chosen as the research design. The aim of qualitative research is to gain an understanding of the phenomena associated with the research subject. Extracurriculars at SMA Muhammadiyah 2 Al-Mujahidin Balikpapan can improve student achievement at school. Because extracurriculars are very necessary in supporting student learning.